PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DALAM UPAYA PENCEGAHAN KENAKALAN REMAJA - Perdana, Novrian Satria (Prodi Teknologi Pendidikan, 2018)
Abstract. Many cases of juvenile delinquency that occurred in the community allegedly be-cause there are lack of exemplary and intensive supervision in our educational and community components. According to this reality, it is urgent to know the strategy of strengthening character education in schools to prevent juvenile delinquency. The purpose of this paper is to examine strat-egies in preventing juvenile delinquency through strengthening character education. This paper uses the theory of habituation from the Skinner, such as spontaneous activities, exemplary meth-ods are also a series of behaviorism theory from John Watson, and conditioning activities that are similar to behaviorism theory from Edwin Guthrie . This study includes the type of literature study research by finding reference theory that relevant to the cases or problems found. The data that have been obtained then analyzed by descriptive analysis method. The conclusions from this litera-ture study includes 1) education in Indonesia still focused on cognitive aspect or academic, while the aspect of soft skills or non academic which is the main element of character education so far still get less attention. 2) implementation of strategies to strengthen character education in schools in preventing juvenile delinquency, can be integrated into existing subjects, local content, self-development. 3) the headmaster as the leader of the school organization is fully responsible for the character building of students, so as a model school requires special efforts to integrate the values of character into the learning process and routine activities in schools. Based on the above conclu-sions, some suggestions were formulated: 1) learning in schools should focus on soft skills or non academic (affective and psychomotor) which are the main elements of character education through teaching and learning activities or extracurricular activities; 2)The national education ministries should formulate learning models that use the character component as the largest com-ponent; 3) the national education ministry should cooperate with TNI and POLRI by conducting education to defend the country that there are character and nationalism elements.Â Abstrak. Maraknya kasus kenakalan remaja yang terjadi di masyarakat diduga ku-rangnya keteladanan dan pengawasan intensif dari komponen pendidikan dan masyarakat. Ber-dasarkan hal tersebut, mendesak untuk diketahui strategi penguatan pendidikan karakter di sekolah dalam mencegah kenakalan remaja. Berdasarkan hal tersebut, tujuan penulisan ini adalah untuk mengkaji strategi dalam mencegah kenakalan remaja melalui penguatan pendidikan karakter. Penulisan ini menggunakan teori pembiasaan dari Skinner, berupa kegiatan-kegiatan spontan, metode keteladanan yang juga sejalan dengan teori behaviorisme dari John Watson, dan kegiatan pengkondisian yang sejalan dengan teori behaviorisme dari Edwin Guthrie. Penelitian ini termasuk jenis penelitian studi literatur dengan mencari referensi teori yang relefan dengan kasus atau per-masalahan yang ditemukan. Data-data yang sudah diperoleh kemudian dianalisis dengan metode analisis deskriptif. Kesimpulan dari studi literatur ini antara lain: 1) Pendidikan di Indonesia masih terfokus pada aspek-aspek kognitif atau akademik, sedangkan aspek soft skills atau non-akademik yang merupakan unsur utama pendidikan karakter selama ini masih kurang mendapatkan per-hatian; 2) Implementasi strategi penguatan pendidikan karakter di sekolah dalam upaya pencega-han kenakalan remaja dapat diintegrasikan ke dalam mata pelajaran yang sudah ada, muatan lokal, pengembangan diri, dan budaya sekolah, dan 3) Kepala sekolah sebagai pemimpin organisasi sekolah bertanggungjawab penuh terhadap pembinaan karakter peserta didik, sehingga sebagai teladan sekolah diperlukan upaya khusus untuk mengintegrasikan nilai-nilai karakter ke dalam proses pembelajaran dan aktivitas rutin di sekolah.. Berdasarkan kesimpulan di atas, dirumuskanbeberapa saran: 1) Pembelajaran di sekolah sebaiknya diutamakan menekankan pada soft skills atau non-akademik (afektif dan psikomotorik) yang merupakan unsur utama pendidikan karakter melalui KBM dan kegiatan ekstrakurikuler; 2) Kemendikbud sebaiknya merumuskan model penilaian yang menggunakan komponen karakter sebagai komponen terbesar; 3) Kemendikbud bekerjasama dengan TNI dan POLRI sebaiknya mengadakan pendidikan bela Negara yang dida-lamnya memuat unsur budi pekerti dan nasionalisme.